Trend of Big Chili Prices in Makassar City Using the Arimax Method: Trend Harga Cabai Besar di Kota Makassar Menggunakan Metode Arimax - Andi Amran Asriadi Andi Alifa; Firmansyah; Nailah Husain (Universitas Merdeka Madiun, 2024)
The aims of the study were (1) to analyze the price forecasting of large chilies based on Arima, (2) to analyze the parameter estimates in the best arima model which can be used to select the best Arima in Makassar City. The type of data used is quantitative data or secondary data. Secondary data in this study were obtained from the official website of the National Strategic Food Price Information Center. The data analysis used is an analysis of the ARIMA forecasting model using EViews12 Statistics. The results of the research are large chili price forecasting based on Arima, the results of the Augmented Dicky Fuller (ADF) test show the statistical value of ADF |-6.513855| > critical value|-2.912631| at the 5% level. (2). The results of the accuracy of the ARIMAX forecasting model on large chili price data in Makassar City using the out-sample criteria, obtained the Mean Square Error (MSE) value. The model chosen is Model (1.1.1), which has the largest MSE of 15510.83, Model (4.0.0), which is the most moderate, has an MSE of 13867.02, and Model (4.1.1) which has the smallest MSE of 13839.57. All P-Value numbers for the regression coefficients, both the ARIMA Models (1.1.1), (4.0.0), (4.1.1) are all below the number ? = 0.05%.